Improving corporate governance with functional diversity on FTSE 350 boards: directors' perspective. Issue 2 (11th November 2019) - Goyal, Rita; Kakabadse, Nada; Kakabadse, Andrew
Abstract : Purpose: Boards presently are considered the most critical component in improving corporate governance (CG). Board diversity is increasingly being recommended as a tool for enhancing firm performance. Academic research and regulatory action regarding board diversity are focussed mainly on gender and ethnic composition of boards. However, the perspective of board members on board diversity and its impact is mostly missing. Moreover, while strategic leadership perspective suggests that a broader set of upper echelon's characteristics may shape their actions, empirical evidence investigating the impact of less-explored attributes of diversity is almost non-existent. While the research on the input–output relationship between board diversity and firm performance remains equivocal, an intervening relationship between board diversity and board effectiveness needs to be understood. The purpose of this paper is to address all three limitations and explore the subject from board members' perspective. Design/methodology/approach: The paper presents the findings of qualitative, exploratory research conducted by interviewing 42 board members of FTSE 350 companies. The data are analysed thematically. Findings: The findings of the research suggest that board members of FTSE 350 companies consider the diversity of functional experience to be a critical requirement for boards' role-effectiveness. Functionally diverse boards manage external dependencies more effectively and challenge assumptions of the executive more efficiently, thus improving CG. The findings significantly contribute to the literature on board diversity, as well as to strategic leadership theory and other applicable theories. The research is conducted with a relatively small but elite and difficult to approach set of 42 board members of FTSE 350 companies. Practical implications: The paper makes a unique and significant contribution to praxis by presenting the perspective of practitioners of CG – board members. The findings may encourage board nomination committees to seek board diversity beyond the gender and ethnic characteristics of directors. The findings may also be relevant for policy formulation, as they indicate that functionally diverse boards have improved effectiveness in a range of board roles. Social implications: Board diversity is about building a board that accurately reflects the make-up of the population and stakeholders of the society where the company operates. The aim of board diversity is to cultivate a broad range of attributes and perspectives that reflects real-world demographics as boards need to continue to earn their "licence to operate in society" as organisations have a responsibility to multiple constituents and stakeholders, including the community and the wider society within which they exist. Building social capital through diversity has value in the wider context of modern society and achieving social justice. Originality/value: The paper makes an original and unique contribution to strategic leadership theory by strengthening the argument of the theory. The paper explores beyond widely researched attributes of gender and ethnicity on boards and explores the impact of a less-researched characteristic of directors – their functional experience. Moreover, the paper opens the "black box" of CG – boards, and presents the perspectives of board members. The findings indicate that board members in FTSE 350 boards define diversity more broadly than academics and regulatory agencies often do.